Association between IgM Anti-Herpes Simplex Virus and Plasma Amyloid-Beta Levels - Féart, Catherine (Public Library of Science, 2011)
OBJECTIVE: Herpes simplex virus (HSV) reactivation has been identified as a possible risk factor for Alzheimer's disease (AD) and plasma amyloid-beta (Aβ) levels might be considered as possible biomarkers of the risk of AD. The aim of our study was to investigate the association between anti-HSV antibodies and plasma Aβ levels. METHODS: The study sample consisted of 1222 subjects (73.9 y in mean) from the Three-City cohort. IgM and IgG anti-HSV antibodies were quantified using an ELISA kit, and plasma levels of Aβ(1–40) and Aβ(1–42) were measured using an xMAP-based assay technology. Cross-sectional analyses of the associations between anti-HSV antibodies and plasma Aβ levels were performed by multi-linear regression. RESULTS: After adjustment for study center, age, sex, education, and apolipoprotein E-e4 polymorphism, plasma Aβ(1–42) and Aβ(1–40) levels were specifically inversely associated with anti-HSV IgM levels (β = −20.7, P = 0.001 and β = −92.4, P = 0.007, respectively). In a sub-sample with information on CLU- and CR1-linked SNPs genotyping (n = 754), additional adjustment for CR1 or CLU markers did not modify these associations (adjustment for CR1 rs6656401, β = −25.6, P = 0.002 for Aβ(1–42) and β = −132.7, P = 0.002 for Aβ(1–40;) adjustment for CLU rs2279590, β = −25.6, P = 0.002 for Aβ(1–42) and β = −134.8, P = 0.002 for Aβ(1–40)). No association between the plasma Aβ(1–42)-to-Aβ(1–40) ratio and anti-HSV IgM or IgG were evidenced. CONCLUSION: High anti-HSV IgM levels, markers of HSV reactivation, are associated with lower plasma Aβ(1–40) and Aβ(1–42) levels, which suggest a possible involvement of the virus in the alterations of the APP processing and potentially in the pathogenesis of AD in human.